KAJIAN LITERATUR SISTEMIK : TEKNOLOGI DIGITAL DALAM MENILAI HALUSINASI - Hardi, Aswin (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021, 2021)
In serving patients, especially patients with psychotic disorders, nurses are faced with situations where patients experience hallucinations. Severe hallucinatory behavior is sometimes easily assessed, but the symptoms of hallucinations are vague and mild, sometimes escape observation. Digital technology developed both audio and visual as well as Virtual Reality can quickly assess the appearance of hallucinatory symptoms, monitor hallucinatory behavior, thereby preventing hallucinations from becoming severe and preventing recurrence. Finally, the patient can get past the hallucinations that appear, and it is easy for the family to seek medical care as soon as possible if they know the behavior of the patient who is experiencing hallucinations early. This literature review aims to describe the development of digital technology in the assessment of hallucinations. This study uses a literature review method. The databases used are ScienceDirect, Scopus, Spingerlink and Oxford Journals. Articles with several keywords, such as hallucinations assessment, hallucinations, hallucinations assessment digital technology. The use of digital technology in assessing hallucinations can improve the quality of care. Further development in digital technology is needed to assess hallucinatory symptoms. Keywords : hallucination, “hallucination assessment”, “hallucination assessment digital technology”